Psychological and Ideological Basis of Collaboration in the Conditions of Russian Aggression in Ukraine - Fris, Pavlo (Review of European and Comparative Law, 2023)
Russia’s aggression against Ukraine gave rise to many problems, including in the field of legislative regulation and protection of the most important social relations, interests, benefits and values recognized as such by the society. At the same time, actions to which the legislation did not pay due (and sometimes no) attention were included in the circle of interests. Among such objects of protection and regulation by criminal law was collaborative activity. It should be noted that not only the criminal law of Ukraine, but also the criminal law of almost all European countries did not form the concept of collaborative activity and did not determine responsibility for it. Most often, collaborative activity was covered by the concept of “treason” without any further differentiation. Even among legal theorists to this day, there is no unity in the understanding of this phenomenon. The author notes that this problem is outside the scope of this publication and is not the subject of the discussion. A number of scientific publications in the Ukrainian scientific space have been dedicated to it. This study focuses on the criminal-legal basis of the legal awareness of people who have committed the actions provided for in Art. 1111 of the Criminal Code of Ukraine, which defines its concepts as well as psychological and ideological foundations that define it.